Resveratrol Improves Bnip3-Related Mitophagy and Attenuates High-Fat-Induced Endothelial Dysfunction - Li, Chen; Tan, Ying; Wu, Jiandi; Ma, Qinghui; Bai, Shuchang; Xia, Zhangqing; Wan, Xiaoliang; Liang, Jianqiu (Frontiers in Cell and Developmental Biology, 2020)
Statin treatment reduces cardiovascular risk. However, individuals with well-controlled low-density lipoprotein (LDL) levels may remain at increased risk owing to persistent high triglycerides and low high-density lipoprotein cholesterol. Because resveratrol promotes glucose metabolism and mitigates cardiovascular disorders, we explored its mechanism of protective action on high-fat-induced endothelial dysfunction. Human umbilical venous endothelial cells were treated with oxidized LDL (ox-LDL) in vitro. Endothelial function, cell survival, proliferation, migration, and oxidative stress were analyzed through western blots, quantitative polymerase chain reaction, ELISA, and immunofluorescence. ox-LDL induced endothelial cell apoptosis, proliferation arrest, and mobilization inhibition, all of which resveratrol reduced. ox-LDL suppressed the activities of mitochondrial respiration complex I and III and reduced levels of intracellular antioxidative enzymes, resulting in reactive oxygen species overproduction and mitochondrial dysfunction. Resveratrol treatment upregulated Bnip3-related mitophagy and prevented ox-LDL-mediated mitochondrial respiration complexes inactivation, sustaining mitochondrial membrane potential and favoring endothelial cell survival. We found that resveratrol enhanced Bnip3 transcription through hypoxia-inducible factor 1 (HIF1) and 5' AMP-activated protein kinase (AMPK). Inhibition of AMPK and HIF1 abolished resveratrol-mediated protection of mitochondrial redox balance and endothelial viability. Together, these data demonstrate resveratrol reduces hyperlipemia-related endothelial damage by preserving mitochondrial homeostasis.